Movie Recommendation Framework Based on Users Interests for Online Social Networks - Dhawan, Sanjeev; Singh, Kulvinder; Singh, Neha (International Journal of Computer Sciences and Engineering, 2025)
Social Networks are networks which provides platform to different users to share their thoughts and make new friends also recommend some products, movies and friends to their friends or any other new users. In today’s environment it is very difficult to suggest a friend to watch what kind of movie on the basis of their interest. To overcome this kind of problem in this paper an attempt has been made to propose a mechanism to recommend a movie to friends based on their interest. The proposed mechanism is assessed using weka tool. This paper is divided into six sections. In section i brief introduction of social networks and recommendation has been discussed, in section ii existing recommendation techniques with their challenges has been presented, section iii covers modern recommendation techniques after that in section iv challenges and issues of different recommendation techniques has been studied in section v proposed mechanism has been presented section vi covers results and analysis of proposed work with weka tool.